Long-Term Observation of Triplex Surgery for Cataract after Phakic 6H Implantation for Super High Myopia - Xin Liu; Fan Fan; Xiaoying Wang; Yi Lu; Tianyu Zheng; Peng Zhou; Xingtao Zhou; Yi Luo (Journal of Ophthalmology)
Purpose. To analyze the safety, effectiveness, and stability of triplex surgery for phakic 6H anterior chamber phakic intraocular lens explantation and phacoemulsification with in-the-bag IOL implantation for super high myopia in long-term observations. Methods. This retrospective case series evaluated 16 eyes of 10 patients who underwent triplex surgery. Best corrected visual acuity (BCVA), endothelial cell density (ECD), and associated adverse events were evaluated. Results. The mean follow-up time after the triplex surgery was 46 ± 14 months. The mean logMAR BCVA was significantly improved after triplex surgery (P = 0.047). One eye developed endophthalmitis five days postoperatively and underwent pars plana vitrectomy (PPV). Five eyes with preoperative severe endothelial cell loss developed corneal decompensation and underwent keratoplasty at a mean time of 9.4 ± 2.6 months after the triplex surgery. One eye had graft failure and underwent a second keratoplasty. The eye developed rhegmatogenous retinal detachment and underwent PPV with silicone oil 18 months later. ECD before the triplex surgery was not significantly different compared with that at last follow-up (P = 0.495) apart from these five eyes. Three eyes (18.8%) developed posterior capsule opacification. Conclusions. Triplex surgery was safe and effective for phakic 6H related complicated cataracts. Early extraction before severe ECD loss is recommended.